(untitled) (Journal of Naval Architecture and Marine Engineering, 2024)
An investigation is made to discuss the effects of Magnetohydrodynamic and nanofluid particles on unstable two-dimensional free convective flow through a vertical plate in the existence of thermal source, radiation effect, and chemical reaction effect with varying thermal and mass flux. The guiding unsteady equations were cracked using the implied finite-difference method. Here we considered four dissimilar nanofluids including Cu, Al2O3, TiO2, and Ag with water as base fluid. The flow pattern employed incorporates the result of dissimilar non-dimensional parameters for instance volume fraction, magnetic field, heat source parameter, Prandtl number, radiation effect, Schmidt number, and chemical reaction effect. The impacts of the above-mentioned parameters on the boundary layer flow characteristics (velocity, temperature, concentration, skin friction coefficient, Nusselt number, and Sherwood number) are intentional. The impact of the velocity profile is highest in silver-water nanofluids and lowest in Al2O3 water nanofluids among the nanofluids considered in this study but the reverse trend is observed with respect to temperature. Moreover, the outcomes are explained through graphs. Journal of Naval Architecture and Marine Engineering, 21(1), 2024, P: 15- 26